Effects of repeated binge intake of the pyrovalerone cathinone derivative 3,4-methylenedioxypyrovalerone on prefrontal cytokine levels in rats – a preliminary study - Nagy, Erin K.; Leyrer-Jackson, Jonna M.; Hood, Lauren E.; Acuña, Amanda M.; Olive, M. Foster (Frontiers in Behavioral Neuroscience, 2023)
Drugs of abuse activate neuroimmune signaling in addiction-related regions of the brain, including the prefrontal cortex (PFC) which mediates executive control, attention, and behavioral inhibition. Traditional psychostimulants including methamphetamine and cocaine are known to induce PFC inflammation, yet the effects of synthetic cathinone derivatives are largely unexplored. In this study, we examined the ability of repeated binge-like intake of the pyrovalerone cathinone derivative 3,4-methylenedioxypyrovalerone (MDPV) to alter cytokine profiles in the PFC. Male and female rats were allowed to intravenously self-administer MDPV (0.05 mg/kg/infusion) or saline as a control under conditions of prolonged binge-like access, consisting of three 96-hr periods of drug access interspersed with 72 hr of forced abstinence. Three weeks following cessation of drug availability, PFC cytokine levels were assessed using antibody arrays. Employing the unsupervised clustering and regression analysis tool CytoMod, a single module of co-signaling cytokines associated with MDPV intake regardless of sex was identified. With regards to specific cytokines, MDPV intake was positively associated with PFC levels of VCAM-1/CD106 and negatively associated with levels of Flt-3 ligand. These findings indicate that prolonged MDPV intake causes changes in PFC cytokine levels that persist into abstinence; however, the functional ramifications of these changes remain to be fully elucidated.